Peptidases in Drosophila melanogaster. - Hall, N.A. (Biochemical Genetics, 1986)
Four major peptidases of Drosophila melanogaster have been described and distinguished by their electrophoretic mobilities, molecular weights, net electrical charges, and substrate specificities. The previously described leucine aminopeptidase, LAP D, consists of at least two isozymes, designated here LAP P and LAP G. In pupae most LAP activity results from LAP P (pupal); in larvae and adults, in contrast, most LAP activity results from LAP G (gut). These two LAPs may be separated by electrophoresis in the presence of the nonionic detergent Triton X-100. A specific assay for LAP P, which exploits the large difference between the net electrical charge of LAP P and that of LAP G, is described. The activity levels of two dipeptidases, Dip A and Dip B, were high in all the postembryonic stages examined. Specific assays for Dip A and Dip B were used to show that for each of these isozymes, the activity in an adult is proportional to gene dosage.